ANALISIS TINGKAT KESEHATAN KOPERASI JASA KEUANGAN SYARIAH NI’MAH - Amnuadin Akbar; Yohana Febiani Angi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
ABSTRACT The cooperative health assessment is an activity that measures the cooperative health levels periodically. The research is meant to know rute of financial services cooperative syariah ni’mah years of book 2015-2019. The date gathering technique for this research is interviews and documenting. Data analysis stars from calculating the score each aspect, quantifying the score overall and doing the trend analysis. Research shows that in the year 2015-2019 there was no maximum score, because there were several aspects which had not yet reached a high of the quality of productive activity, of management, of efficiency, of liquidity, of cooperative identit, of selfreliance and growth, and of syariah principle compliance. Keywords: Health of islamic financial services operatives.